Yield and Zn content of biofortified rice genotypes in an Indonesian rice agro-ecosystem - UNTUNG SUSANTO; UMI BAROKAH; AKHMAD HIDAYATULLAH; SATOTO SATOTO; MALIKARJUNA SWAMY (Smujo International, 2017)
Susanto U, Barokah U, Hidayatullah A, Satoto, Swamy M. 2017. Yield and Zn content of biofortified rice genotypes in an Indonesian rice agro-ecosystem. Nusantara Bioscience 9: 288-294. Approximately one-third of the world's population suffer from Zn deficiency causing significant socio-economic losses as a result of stunting and compromised immune system function. One strategy to overcome the problem is by developing rice cultivars with high grain Zn content (Zn Rice) to improve dietary intake.This study reports the yield and Zn content of 22 rice genotypes developed at the International Rice Research Institute (IRRI) and the Indonesian Centre for Rice Research (ICRR).The experiment was conducted in the Cirebon district of West Java province during the 2013 wet season (2013WS). Yield and grain Zn content (using an XRF machine) were measured. Five lines demonstrated higher yield (ranging from 7.0 to 8.9 t/ha) than the check variety Ciherang (5.2 t/ha), but had similar grain Zn content to the check variety Ciherang (23.4 ppm), ranging from 19.0 to 24.8 ppm. On the other hand, seven lines had higher grain Zn content (ranging from 30.0 to 34.2 ppm) compared to Ciherang, and five of these lines had comparable yield to Ciherang. The selected lines had acceptable agronomic traits, and are suitable for further testing and utilization, in addition to providing a foundation for future improvement in the dual goals of increasing the yield and nutritional value of rice.